Role of nasal microbiota in regulating host anti-influenza immunity in dogs - Jinzhu Geng; Yuhao Dong; Hao Huang; Xia Wen; Ting Xu; Yanbing Zhao; Yongjie Liu (Microbiome)
Abstract Background Numerous studies have confirmed a close relationship between the pathogenicity of influenza and respiratory microbiota, but the mechanistic basis for this is poorly defined. Also, the majority of these studies have been conducted on murine models, and it remains unclear how far these findings can be extrapolated from murine models to other animals. Considering that influenza A virus is increasingly recognized as an important canine respiratory pathogen, this study investigated the cross-talk between nasal and lung tissues mediated by microbes and its association with influenza susceptibility in a beagle dog model. Results Using 16S rRNA gene sequencing, combined with comparative transcriptomic, anatomical, and histological examinations, we investigated viral presence, gene expression profiles, and microbiota in the nasal cavity and lung after influenza infection in the beagles with antibiotic-induced nasal dysbiosis. Our data showed that dysbiosis of the nasal microbiome exacerbates influenza-induced respiratory disease and the epithelial barrier disruption, and impairs host antiviral responses in the nasal cavity and lung. Moreover, dysregulation of nasal microbiota exacerbates the influenza-induced disturbance in lung microbiota. Further, we also identified a strain of Lactobacillus plantarum isolated from canine nasal cavity with a significant antiviral effect in vitro, and found that its antiviral activity might be associated with the activation of the interferon (IFN) pathway and modulation of the impaired autophagy flux induced by influenza infection. Conclusions Our investigation reveals that nasal microbiota dysbiosis exerts a prominent impact on host antiviral responses, inflammation thresholds, and mucosal barrier integrity during influenza infection. Lactobacilli, as part of the nasal microbiota, may contribute to host antiviral defenses by modulating the IFN and autophagy pathways. Collectively, this study underscores the importance of nasal microbiota homeostasis in maintaining respiratory health. Video Abstract